1987
DOI: 10.1111/j.1756-1051.1987.tb00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in leaf lipids of Diapensia lapponica, with special reference to storage lipid bodies

Abstract: Seasonal fluctuations in storage lipids in the cushion plant Diapensia lapponico, growing in Northern Finland (70"N 27"E). were studied by microscopy and chemical analysis. Lipid bodies in the mesophyll cells were stained with Sudan Black for quantitative observation by light microscope. Electron microscope observations were made using aldehyde prefixed and osmium tetroxide postfixed sections of leaf blades. Thin layer and gas capillary chromatographic techniques were used to analyse total lipids and total fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
1
Order By: Relevance
“…Pihakaski et al (1987) reviewed some of the literature about this and showed that a sclerophyllous, evergreen cushion plant of arctic and subarctic regions, Diapensia lapponica (Diapensiaceae), has a single large lipid body in each mesophyll cell during warmer months, but many smaller lipid bodies per mesophyll cell during cold months. They speculated that this change helps to lower the freezing point of cells.…”
Section: Oil Body Occurrence In Leaf Cells-why Have Oil Bodies In Leamentioning
confidence: 98%
“…Pihakaski et al (1987) reviewed some of the literature about this and showed that a sclerophyllous, evergreen cushion plant of arctic and subarctic regions, Diapensia lapponica (Diapensiaceae), has a single large lipid body in each mesophyll cell during warmer months, but many smaller lipid bodies per mesophyll cell during cold months. They speculated that this change helps to lower the freezing point of cells.…”
Section: Oil Body Occurrence In Leaf Cells-why Have Oil Bodies In Leamentioning
confidence: 98%
“…Also, it was thought possible that they might function as short-term storage of photosynthetic products where assimilates being stored in them during periods of peak photosynthesis and metabolized, for example, during the night [4]. Another possible function for oleosomes is adaptation to environmental stress such as salinity [5], cold temperature [6] and fungal infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…Only the moss Physcomitrella patens (three paralogs) and the primitive fern (fern ally; Selaginella moellendorffii; eight paralogs) possess genes encoding oleosins. Primitive plants, including bryophytes (mosses) and ferns, contain neutral lipids and OBs (Swanson et al, 1976;Pihakaski et al, 1987;Dembitsky, 1993). We chose the more primitive Physcomitrella for intensive study.…”
mentioning
confidence: 99%